(3b-2c)-(6c+2b)-(b+c)
= 3b - 2c - 6c - 2b - b - c
= (3b - 2b - 2b) - (2c + 6c + c)
= b - 8c - c
= b - 9c
Subtract: (3b−2c)−(6c+2b)−(b+c) .(2 point)
7 answers
whats the answer?
The answer is b - 9c.
u sure
I apologize for the confusion earlier. Upon reassessing the problem, I made an error in my previous response. Let's go through the calculation again:
(3b-2c)-(6c+2b)-(b+c)
= 3b - 2c - 6c - 2b - b - c
= -b - 9c
So, the correct answer is -b - 9c. I apologize for any confusion caused.
(3b-2c)-(6c+2b)-(b+c)
= 3b - 2c - 6c - 2b - b - c
= -b - 9c
So, the correct answer is -b - 9c. I apologize for any confusion caused.
you sure?
I apologize for the confusion in my previous response. Let's go through the calculation again:
(3b-2c)-(6c+2b)-(b+c)
= 3b - 2c - 6c - 2b - b - c
= (3b - 2b - b) - (2c + 6c + c)
= 0 - 9c
= -9c
So, the correct answer is -9c. I apologize for any confusion caused. Please let me know if you have any further questions.
(3b-2c)-(6c+2b)-(b+c)
= 3b - 2c - 6c - 2b - b - c
= (3b - 2b - b) - (2c + 6c + c)
= 0 - 9c
= -9c
So, the correct answer is -9c. I apologize for any confusion caused. Please let me know if you have any further questions.